Creativity and Critique in Online Learning Exploring and Examining Innovations in Online Pedagogy (Springer International Publishing, 2018)
This book explores emerging practices in distance education that have been facilitated by the development of educational technology. The volume examines core themes in distance education including online education at scale, embodiment in online environments, connectivity in online education and the personalisation of learning experiences within online education. The first section of the book examines online teaching tools, and explores how they are being used to enhance and promote student learning. The second looks at some of the broader challenges encountered by online teachers and those responsible for designing online learning material. While this volume will be of significant interest to distance learning universities and colleges, it will also be a valuable resource to traditional Higher Education Institutions, who are increasingly searching for innovative ways to reach and teach their students. This edited collection will be of value to scholars of online education as well as practitioners and policy makers looking to enrich their notions of online pedagogy.